Access to highly active antiretroviral therapy for injection drug users: adherence, resistance, and death - David Vlahov; David D. Celentano
Injection drug users (IDUs) continue to comprise a major risk group for HIV infection throughout the world and represent the focal population for HIV epidemics in Asia and Eastern Europe/Russia. HIV prevention programs have ranged from HIV testing and counseling, education, behavioral and network interventions, drug abuse treatment, bleach disinfection of needles, needle exchange and expanded syringe access, as well as reducing transition to injection and primary substance abuse prevention. With the advent of highly active antiretroviral therapy (HAART) in 1996, dramatic clinical improvements have been seen. In addition, the treatment's impact on reducing HIV viral load (and therefore transmission by all routes) provides a stronger rationale for an expansion of the focus on prevention to emphasize early identification and treatment of HIV infected individuals. However, treatment of IDUs has many challenges including adherence, resistance and relapse to high risk behaviors, all of which impact issues of access and ultimately effectiveness of potent antiretroviral treatment. A major current challenge in addressing the HIV epidemic revolves around an appropriate approach to HIV treatment for IDUs.